limite d'un produit de fonctions

Si lim f(x) = 3 et lim g(x) = 4 alors
On ne peut pas conclure pour la limite du produit
lim ( f(x)g(x) ) = +
lim ( f(x)g(x) ) = -
lim ( f(x)g(x) ) = 12
Si lim f(x) = 3 et lim g(x) = + alors
On ne peut pas conclure pour la limite du produit
lim ( f(x)g(x) ) = +
lim ( f(x)g(x) ) = -
lim ( f(x)g(x) ) = 3
Si lim f(x) = - et lim g(x) = + alors
On ne peut pas conclure pour la limite du produit
lim ( f(x)g(x) ) = +
lim ( f(x)g(x) ) = -
lim ( f(x)g(x) ) = 0
Si lim f(x) = -5 et lim g(x) = - alors
On ne peut pas conclure pour la limite du produit
lim ( f(x)g(x) ) = +
lim ( f(x)g(x) ) = -
lim ( f(x)g(x) ) = -5
Si lim f(x) = + et lim g(x) = + alors
On ne peut pas conclure pour la limite du produit
lim ( f(x)g(x) ) = +
lim ( f(x)g(x) ) = -
lim ( f(x)g(x) ) = 0
Si lim f(x) = - et lim g(x) = - alors
On ne peut pas conclure pour la limite du produit
lim ( f(x)g(x) ) = +
lim ( f(x)g(x) ) = -
lim ( f(x)g(x) ) = 0
Si lim f(x) = + et lim g(x) = 0 alors
On ne peut pas conclure pour la limite du produit
lim ( f(x)g(x) ) = +
lim ( f(x)g(x) ) = -
lim ( f(x)g(x) ) = 0
Si lim f(x) = - et lim g(x) = 0 alors
On ne peut pas conclure pour la limite du produit
lim ( f(x)g(x) ) = +
lim ( f(x)g(x) ) = -
lim ( f(x)g(x) ) = 0
Si lim f(x) = 0 et lim g(x) = 0 alors
On ne peut pas conclure pour la limite du produit
lim ( f(x)g(x) ) = +
lim ( f(x)g(x) ) = -
lim ( f(x)g(x) ) = 0
Si lim f(x) = -3 et lim g(x) = + alors
On ne peut pas conclure pour la limite du produit
lim ( f(x)g(x) ) = +
lim ( f(x)g(x) ) = -
lim ( f(x)g(x) ) = -3